2012
DOI: 10.1073/pnas.1209367109
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral delivery of self-amplifying RNA vaccines

Abstract: Despite more than two decades of research and development on nucleic acid vaccines, there is still no commercial product for human use. Taking advantage of the recent innovations in systemic delivery of short interfering RNA (siRNA) using lipid nanoparticles (LNPs), we developed a self-amplifying RNA vaccine. Here we show that nonviral delivery of a 9-kb self-amplifying RNA encapsulated within an LNP substantially increased immunogenicity compared with delivery of unformulated RNA. This unique vaccine technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
528
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 552 publications
(567 citation statements)
references
References 38 publications
7
528
0
11
Order By: Relevance
“…Previously, we have shown that this imaging system could detect bioluminesce after the i.m. administration of a SAM vector encoding luciferase, and bioluminescence persisted for almost 2 mo after vaccination (10).…”
Section: Early In Vivo Ag Expression At Site Of Injectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have shown that this imaging system could detect bioluminesce after the i.m. administration of a SAM vector encoding luciferase, and bioluminescence persisted for almost 2 mo after vaccination (10).…”
Section: Early In Vivo Ag Expression At Site Of Injectionmentioning
confidence: 99%
“…Ag-expressing (or reporter geneexpressing) replicons derived from the Venezuelan equine encephalitis virus genome containing the 39 untranslated region and packaging signal of Sindbis virus (SV) were electroporated into BHK cells along with defective helper RNAs encoding the SV capsid and glycoprotein genes (10). VRPs in the culture media were harvested and titrated.…”
Section: Vaccine Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…siRNA may also be used for therapeutic purpose like vaccine and chemical drugs. 9 Our present study is aimed to design a potential siRNA for inhibiting the translation of this ICP22 (US1) gene and hinder the overall replication process.…”
Section: Introductionmentioning
confidence: 99%